The potential of virtue ethics in ethical education in Slovakia - Baďurová, Barbora (Array, 2019)
Virtue ethics is an approach to normative ethics that emphasizes the great character traits of moral agents. As many authors have pointed out, this approach also has great potential in contemporary ethical education. The following text will focus on the possibility practically utilising virtue ethics in ethical education in Slovakia. One of the most influential figures in the development of this topic in Slovakia is Ladislav Lencz, who also created key texts for teachers of ethical education. His concept is based primarily on a pedagogical and psychological basis, inspired by Spanish psychologist R.R. Olivar’s concept of prosociality. However, some of L. Lencz’s texts also display elements of virtue ethics. This article will point out the possibilities of implementing virtue ethics in ethical education.